Making a Visible Difference in Our Wrld - Global Environment Facility (Washington, DC, 2013)
Like the 2003 Fifth World Parks Congress in Durban, South Africa, this publication is structured around themes and issues on the cutting edge of research, policy, and practice in the field of protected areas. It highlights contributions by the Global Environment Facility (GEF) and presents its perspectives for the future. This publication comprises of the following topics : Tribute to Africa; A Historic Role for Protected Areas; Protected Areas and The GEF; Links to Land and Sea; Protected Areas In the Mainstream; New Ways of Working Together; Developing the Capacity to Manage; Maintaining Protecting Areas Now and In the Future; Building A Secure Financial Future; Constructing Comprehensive Protected Area Systems; Looking Forward: Let Earth Last.